Furry Families: Ethical Entanglements Through More-than-Human Domestic Dramas. (June 2023) - Sayers, Janet; Forrest, Rachel; Pearson, Maria
Companion animals (CA) are seen as part of the family by their human guardians. However, guardians' intense attitudes towards CA can lead to tensions with larger society. Recent scholarship has argued for more critical work exploring interspecies family relations. The present research is framed by previous scholarship exploring CA family relations and the role that storytelling about animals plays in developing ethical relations with animals. We examine 369 stories told by guardians of companion animals as part of a One Welfare study examining attitudes to companion animal welfare. Our analytical frame was a genre discourse approach sensitive to questions of animal ethics. Our theoretical contribution is to contribute a new sub-genre of domestic drama, more-than-human domestic drama. We explore the implications of this genre of family stories and why it matters beyond families to wider society.